Exploring the Role of Emotional Intelligence and Self-Confidence in Supporting Islamic Religious Education Learning Outcomes - Salim, M Agus; Rajabiyah, Nurlaila; Misrodin, Misrodin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to investigate the effect of emotional intelligence (EI) and self-confidence on students' academic achievement in Islamic religious education, as well as evaluate the interaction between the two variables and provide strategic recommendations for educators to improve student learning outcomes. Methodology: The method used in this research is quantitative with ex post facto design. The research sample consisted of 35 students of the Early Childhood Education Teacher Education (PG-PAUD) Study Program at STKIP Kumala Lampung. Data were collected through questionnaires measuring emotional intelligence (EI), self-confidence (SC), and student learning outcomes, and data were analyzed using ANOVA and paired-samples t-test. Main Findings: The results showed a significant relationship between emotional intelligence (EI) and self-confidence (SC) on student learning outcomes. Students who have high levels of emotional intelligence and self-confidence tend to achieve better learning outcomes, with the average learning outcome reaching 78.90, compared to students who have low levels of emotional intelligence and self-confidence which only reach 66.95. This finding confirms the importance of emotional intelligence and self-confidence development in the context of Islamic religious education. Novelty/Originality of this study: The uniqueness of this study lies in its focus on the influence of emotional intelligence (EI) and self-confidence (SC) in the context of Islamic religious education, which is still less explored in the literature. This research provides new insights that are useful for improving teaching strategies, supporting student development, as well as enriching existing knowledge in the field of Islamic religious education.